A produção acadêmica de Marketing no Brasil : uma análise historiográfica dos últimos 50 anos - Costa, César Renato Ferreira da (2008)
The marketing, as a phenomenon of social and applied sciences, is the product of a scientific-theoretical social construction for over a century in the administrative thought, being integrated in the interest of other areas of science insofar as it increases its volume of social influence. Considered the circumstances of the market such as exchange and relationship the phenomenon can be identified by the study of civilization since its existence. With an academic and scientific perspective, it emerges from the transformative social revolutions of the eighteenth century and has evolved its theoretical framework to the present, having passed through several interpretative phases. The global marketing as understood at present is the product of an original construction from several theoretical schools, especially of Anglo-American origin, notably intensive in the United States. This work, considering these original circumstances and their influences, studies the phenomenon since its emergence in the academies of higher education in Brazil until its present. From sources that reveal the academic production of marketing in Brazil, this paper researches if there is a marketing that can be identified as Brazilian or whether what we have in the country only reflects a construction imported from other cultures. One method based on historical analysis of events and publications, published in the last 54 years and an exploratory research with teachers in the area, build an information base for conclusive considerations of the proposed questioning. The final answer to this question is pointed from the information taken, crossed with the concept of prevailing paradigms for the current marketing and is defined in this work like a reproduction of american and european paradigms to studies of marketing.